(untitled) (Journal of Enam Medical College, 2012)
Background: Lymphadenopathy is a common manifestation of a large variety of disorders,both benign and malignant. It is essential to define the pattern of disorders presenting primarily as lymph node enlargement in a particular environment. Histopathological examination of the lymph node biopsies is a gold standard test in the distinction between reactive and malignant lymphoid proliferations as well as for detailed subtyping oflymphomas. We designed this study in our population for histopathological evaluation of lymph nodes that might be helpful for clinical management of these lesions. Objective: Histopathological evaluation of lymphadenopathy from excised specimen, in relation to ageand sex of the patients, and distribution of the lymph nodes. Materials and Methods: It was a retrospective cross sectional study conducted in the department of Pathology, Enam MedicalCollege & Hospital, Savar, Dhaka during the period from January 2006 to December 2010. Lymph node biopsies of all patients of both sexes and all age groups were included.Metastatic lymph nodes associated with evidence of primaries elsewhere in the body were excluded from the study. Total 191 lymph node biopsies were selected for histopathological evaluation. Among these 90 (47.12%) were from males and 101 (52.88%) were from females with male to female ratio being 1:2.1. The age of the patients ranged from 2 to 85 years with a mean age of 35.73 ± 18 years. Results: Cervical lymph nodes were the most common (56%) biopsied group. Of the 191 cases 59 cases (30.89%) were reactive lymphadenitis, 64 cases (33.5%) were tuberculosis, 2 cases (1.05%) were non-caseous granuloma, 11 cases (5.76%) were Hodgkin lymphoma, 22 cases (11.52%) were non-Hodgkin lymphoma, 24 cases (12.57%) were metastatic neoplasm and 9 cases (4.7%) were other lesions. Conclusion: Tuberculosis was the most common cause of lymphadenopathy, followed by reactive lymphadenitis and the cervical group of lymph nodes was most frequently affected. DOI: http://dx.doi.org/10.3329/jemc.v2i1.11915 J Enam Med Col 2012; 2(1):8 -14